3‐D Architecture and Plio‐Quaternary Evolution of the Paola Basin: Insights Into the Forearc of the Tyrrhenian‐Ionian Subduction System. Issue 2 (3rd February 2020) - Corradino, M.; Pepe, F.; Bertotti, G.; Picotti, V.; Monaco, C.; Nicolich, R.
Abstract: Using seismic reflection profiles and bathymetric data, we analyzed the stratigraphy and tectonics of the Paola Basin, providing information on the dynamic of the forearc of the Tyrrhenian‐Ionian subduction system. The Paola Basin is a NNW‐SSE trending syncline, bounded by the Coastal Chain to the east and the Paola Anticline to the west. It hosts up to 5.2 km thick Plio‐Quaternary deposits, most of them supplied from Apenninic/Sila entry points and transported by longshore currents. The total subsidence reaches a value of ∼5 km. The sedimentary load varies from 60% to 75% of the total subsidence. The Pliocene to Lower Pleistocene sedimentary infill of the syncline displays a strata growth geometry consistent with a continuous rotation of the eastern limb of the Paola Anticline. Crustal folding can explain both the tectonic subsidence of the Paola Basin and the uplift of the Paola Anticline. To the east of the basin, Late Pliocene to Early Pleistocene growth of the central sector of the Coastal Chain led to the definition of the Paola and Crati basins, previously connected in a larger proto basin. The trench‐parallel component of the plate movement was accommodated by a strike‐slip zone, with associated releasing and restraining bends coinciding with the Paola Anticline. The bathymetric expression of the strike‐slip zone consists of structural highs and depressions that overall form the Paola Ridge. Since the Middle Pleistocene, the growth of the Paola Anticline and Paola Basin came to an end and extensional tectonics controlled the evolution of the forearc region. Key Points: Crustal folding exerts a first‐order control on basin formation and tectonic subsidence of the Paola Basin Sedimentary infill of the Paola Basin shows a strata growth geometry consistent with a folding by limb rotation of the Paola Anticline The Paola Basin is limited westward by a strike‐slip fault zone that accommodates the trench‐parallel component of the upper plate motion